Quando a conexão promove a inovação : as redes de projeto como indutoras de processos de inovação orientadas pelo design estratégico - Filho, Antonio Carlos de Souza Lima (Universidade do Vale do Rio dos Sinos, 2017)
The market challenges organizations to remain working profitably and sustainably. Validated models of management, business and strategy are being put into test by the contemporary economy. Collaboration and networking can help the innovation of business processes mediated by technology. So, integrating knowledge seems to be the new order of organizational survival. In addition, these opportunities, aligns knowledge to guide these new social and business demands: the strategic design. This study shows how can a company that does not operate in the network benefit from the innovation mediated by technology processes.Global business processes that operate in a network under metaproject leadership were selected, extracted categorized and recategorized. Then this company and its several strategic design tools are presented. As a result, elaborated scenarios were built by strategic articulated design bias from the metaprojetual construction of the companies analyzed.
Keywords: Redes de projeto; Design estratégico; Metaprojeto; Inovação dirigida pelo design; Cenários orientados para o design; Project networks; Strategic design; Metaproject; Innovation directed by design; Design-oriented scenarios; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial